PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF LEARNING MOTIVATION OF STUDENTS - Abdullayeva Barno Sayfutdinovna (Scholar Express Journal, 2021)
The need for knowledge is one of the main human needs, on the basis of which the individual masters the centuries-old human experience. At different periods of a person's life, the objects of his interest, forms and methods of acquiring knowledge change, but the need for knowledge as an inherent property of a person, not only does not become dull over the years, but also receives its further development.
Keywords: development; become; receives; individual